2020
DOI: 10.18621/eurj.559681
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of indications and birth results of cesarean section due to ophthalmologic diseases

Abstract: Objectives: To investigate the outcomes of cesarean section due to ophthalmologic indications. Methods: This retrospective clinical study included 40,190 patients underwent cesarean section due to ophthalmological indications between January 2013-August 2015 in MLP Care Group Hospitals (It includes 32 hospitals). Demographic data, ophthalmologic history and indications and surgical outcomes of caesarean section was assessed. Results: Of the 53 patients with caesarean delivery due to ophthalmologic indications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It has also been said that the eye diseases that are the most common indications of CS are myopia, retinopathy, and glaucoma. A review of the articles shows no consensus about planning the delivery method based on eye diseases (20). A recent meta-analysis showed that the vertical transmission rate of human papillomavirus (HPV) in CS is lower than in vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been said that the eye diseases that are the most common indications of CS are myopia, retinopathy, and glaucoma. A review of the articles shows no consensus about planning the delivery method based on eye diseases (20). A recent meta-analysis showed that the vertical transmission rate of human papillomavirus (HPV) in CS is lower than in vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 6 -17% of all births occurring through CS worldwide are based on the mother's request (11). Moreover, 17% of indications for CS are due to non-obstetric reasons (20). The most common non-obstetric causes of CS between 1950 -2017 include cardiovascular and eye diseases (e.g., myopia, diabetic retinopathy, and glaucoma), blood diseases, rheumatology, psychological diseases (e.g., tokophobia), neurological diseases, orthopedic diseases (e.g., herniated disk), and infectious diseases (e.g., genital warts).…”
Section: Introductionmentioning
confidence: 99%